Pendidikan Jasmani Dimulai dari Keluarga - Agus Susworo Dwi Marhaendro (Jurnal Pendidikan Jasmani Indonesia, 2005)
Gender equivalence gives opportunity to woman to compete in work withman. That is still conducted up to the grade of managing the family, so that they are asparents still having some times for much more different outdoors activities. As itsconsequences, they have a different style of nursing children. Based on the statementthat ideal education ought to be done by parents themselves in the family, whereas inthe family there are different patterns in taking care of children, thereby the writermeans to study the parents’ role as educators in family, which is focused in physicaleducation.The physical education in family represents the condition or situation that has to becreated or has to be done. To realize the activity, there are three elements required,that are: doer, time, and location or place. Parents’ role of creating the physical educationin the family’s environment present in their willing to provide times and to chooselocations for the continuity of forms of the physical education activity.Keyword: Physical education, children of early ages, family